Citric acid vapor-assisted crosslinking of zein/PEG composite nanofiber membrane embedded with nisin by electrospinning for the cooled goose meat preservation - Lanlan Wei; Shuaijie Zhu; Guoyuan Xiong; Jingjun Li; Wangang Zhang (Current Research in Food Science, 2025)
This study demonstrated the fabrication of zein/polyethylene glycol/nisin (zein/PEG/nisin) nanofiber membrane and cross-linked by citric acid vapor (zein/PEG/nisin/C). The distribution within the whole nanofiber membranes was monitored by scanning electron microscopy (SEM). Studies using thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) validated the effectiveness nisin encapsulation and molecular interactions. The water vapor permeability (WVP) and oxygen permeability (OP) of zein/PEG/nisin/C are 150.47 ± 7.14 (g m−2 24h) and 59.74 ± 3.10 (cm3 m−2 24h), respectively. Antibacterial experiments have shown that the antibacterial effect of zein/PEG/nisin/C on Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) and the diameters of the bacteriostatic circle were 11.52 ± 0.44 mm and 10.67 ± 0.46 mm, respectively. During 10 days of the storage of the cooled fresh goose meat, compared with the control group, the pH of zein/PEG/nisin/C nanofiber membrane was 5.7, the concentration of the total volatile basic nitrogen (TVB-N) and the value of total viable count (TVC) and thiobarbituric acids (TBARS) are 11.28 mg/100g, 5.01 ± 0.69 log (CFU g−1), and 0.83 mg kg−1, respectively. These results point to the possibility of using functionalized nanofiber membranes for the cold fresh goose meat preservation facilitated by vaporized citric acid cross-linking.